The Comparison of Intelligence Levels between Male and Female Students at SMA Negeri 5 Sorong Regency - Ulfa, Nurul Alia (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This research is an ex post facto study which aims to find out whether there are significant differences in the level of intelligence between male and female students at SMA Negeri 5 Sorong Regency. The population in this study was all students of SMA Negeri 5 Sorong Regency, totaling 157 people, with a total sample of 67 people. The sampling technique used purposive sampling technique. The results showed that there was no significant difference in the level of intelligence between male and female students with sig. (2-tailed) 0.439 at the sig level. α 0.05.